STATUS AGAMA DALAM KEHIDUPAN PUBLIK PERSPEKTIF HAM INTERNASIONAL - Yudi Junadi (Jurnal Hukum Mimbar Justitia, 2020)
Along with the rise of religious claims as one of the solid foundations for the grounding of Human Rights (HAM), the problems confronting humanity in relation to the presence of religion, in the contemporary era tend to escalate. The current wave of globalization has not only marginalized but rather provided an opportunity for the birth of various religious transnational movements that had not been predicted before. The conception of the modern state adopted by the West which was later referred to as a model for the construction of the state in various other parts of the world, was founded on the basis of secular values that transcended traditional solidarity, among which were national equality. Apart from the black stain that has been inscribed in history, especially in the field of freedom of thought, religion at this time can be said to have a positive contribution as a source of aspiration for the parties that are suppressed.Â Keywords : Globalization, Freedom of Religion, International Law, Human Rights.